Dawson’s finger radiological presentation of relapsing remitting multiple sclerosis in a young female: a case report and review of the literature - Hadeel Al-Husban; Stavroula L. Kastora; Olusegun Oduyoye (Journal of Medical Case Reports)
Abstract Background The prevalence of multiple sclerosis in the UK is among the highest in the world with prevalence in the north of Scotland presenting the peak of cases. Pathologically multiple sclerosis is regarded as multifocal areas of demyelination resulting in a spectrum of clinical manifestations, which pose diagnostic challenges. Dawson fingers are periventricular hyperintensities that that display high specificity for multiple sclerosis over all other demyelinating conditions. Intriguingly, they are also seen in cerebral small vessel diseasespectrum maladies. Case presentation In this case report we explore the presentation of Dawson finger hyperintensities in the primary diagnostic magnetic resonance imaging of a 26 year old white caucasian female with right-sided dysesthesia as the presenting complaint of relapsing remitting multiple sclerosis. Conclusion We further assess the sensitivity and specificity of Dawsons fingers upon multiple sclerosis diagnosis as well as their implications in differentiation between a family of demyelinating conditions with similar presentations. Lastly, we highlight the interplay between vascular and neuronal integrity in multiple sclerosis progression as highlighted by imaging and biochemical pathophysiology.